Myocardial infarction-induced acute stress and post-traumatic stress symptoms: the moderating role of an alexithymia trait – difficulties identifying feelings. Issue 1 (31st December 2020) - Ledermann, Katharina; von Känel, Roland; Barth, Jürgen; Schnyder, Ulrich; Znoj, Hansjörg; Schmid, Jean-Paul; Meister Langraff, Rebecca E.; Princip, Mary
ABSTRACT: Background: It has been acknowledged that medical life-threatening experiences such as an acute myocardial infarction (MI) often lead to acute stress disorder symptoms (ASS), which in turn can result in the development of post-traumatic stress symptoms (PTSS). Previous studies have suggested an association between various traumatic experiences and alexithymia. The association of alexithymia with ASS and PTSS in patients with MI is elusive. Objectives: The aim of this study was to examine the association of alexithymia with MI-induced ASS and PTSS in patients at high risk of developing PTSD. Method: Patients ( N = 154) were examined twice, once within 48 hours, and then again three months after acute MI. All patients completed the self-rating Acute Stress Disorder Scale (ASDS) within 48 hours after the cardiac event. Three months after hospital discharge, all patients completed the Toronto Alexithymia Scale (TAS-20) and underwent the Clinician-Administered PTSD Scale (CAPS), a structured interview to assess the severity of PTSS. Descriptive statistics, correlations, multivariate linear regressions, and moderation analysis were conducted. Results: The linear regression model explained 23% of the variance in MI-induced PTSS-symptoms ( F (6.109) = 5.58, p < 0.001, R 2  = 0.23. ASS was significantly related to PTSS severity ( r (152) =  p < 0.001). The scores of the TAS-20 subscale difficulties identifying feelings (DIF) were found to significantly moderate this relationship ( R 2  = 0.03, p = 0.04). The scores of TAS-20 subscales DDF and EOT as well as the TAS-20 total score had no influence on the relationship between ASS and PTSS (p > 0.05). Conclusion: In MI patients with high levels of DIF, ASS predicted the development of PTSS. If replicated, the finding may inform emotion-oriented interventions to investigate whether increasing the capacity to identify feelings following acute MI could be beneficial in preventing the development of PTSS.